The ethics of organ transplantation - Shelton, Wayne N.; Balint, John (Advances in bioethics ;, 2001)
Since the 1970s, we have witnessed astonishing scientific and technical progress in the field of organ transplantation. Patients who suffer organ failure can now often have their lives greatly improved both in terms of quality and quantity of years. The success of transplantation techniques has created an enormous demand for donor organs. Unfortunately, donor organs are in short supply, relative to the number of patients who could greatly benefit from them. Therefore, donor organs are a scarce and valuable resource that must be thoughtfully and fairly allocated among waiting patients. Not surprisingly, this situation raises many pressing ethical questions, each requiring careful consideration. This volume presents a systematic and balanced treatment of some of the most pressing ethical questions including: what is our ethical obligation to become organ donors and who should be allowed to donate; to what extent can markets facilitate the fair allocation of organs and how should we most fairly determine who should be recipients; how do we determine death when the donor is not brain dead; should non-human donor organs be used to save human lives and should we use organs from anencephalic infants and tissue from embryos ; and what is the role of the news media in covering stories about organ transplantation? Many of the leading authorities in medical ethics come together in this volume to develop extensive analyses and arguments. The reader is provided with a sound understanding of the ethical, as well as many of the broader issues in organ donation and transplantation.